A operacionalização dos procedimentos de medidas protetivas a crianças e adolescentes em situação de acolhimento institucional na comarca de Palmas/Tocantins - Vieira, Márcia Mesquita (Universidade Federal do Tocantins, 2016)
The present technical research report deals with the theme of full protection of children and adolescents in the justice system, from the perspective of Human Rights, more specifically, about the operational procedures of institutional care protection measure. In Brazil, the Federal Constitution of 1988 represents a regulatory framework in the fight for the recognition of children and adolescents as subjects of rights, with its materiality anchored in the principles and guidelines the Statute for Children and Adolescents (SCA), specific legislation of attention to this population. The statute was revised and specially modified in the parts relating to the protection of children and adolescents in situations of violation of rights or at risk, resulting in the enactment of Law No. 12,010, of August 3,2009, called Law of Family Living and Communitarian (LFLC ), which sought to improve the guarantees already recommended in previous legislation. In particular, the legal institution of the host was reinterpreted and its operation was redirected with a view to give greater effectiveness in running and five areas of restructuring were prioritized, and the formation of lawsuits for each child received; definition and guidance of enforcement mechanisms and periodic review of the protective measure; joint liability with training and qualification of system professionals; monitor the implementation of services and amenities; and reporting to the National Council of Justice (NCJ).The recommended changes have been established for over six years, but in Palmas / TO judicial district they are still invisible from the empirical point of view, basing the relevance of a systematic study to know the intrinsic issues to such a scenario. Thus the documentary research was carried out by the Court of Childhood and Youth, through specific instruments for data collection, one for each axis of operationalization. Documents produced in 2015 were analyzed to represent the usual procedures nowadays and included 16 host processes, 36 records of concentrated audience, 01 inspection at the host institution report and the records of the National Children Register Received (NCRR), 17 entries received from 17 guides the host, 36 guides and 04 entries shutdown institutions. The lack of training and continuing education plan, so the analysis of this axis is given only in the theoretical and normative field is recorded. For the documents related to other axes the content analysis technique was used, from two categories of analysis, the contradiction and historicity. Difficulties in overcoming the SGD isolated and welfare practices were identified, demonstrating a contradictory picture of violation and protection in the course of the visits. Some specific efforts to reframe the procedures were identified, More specifically in the structuring of lawsuits protection measure, in conducting the hearings and concentrated in data entry in NCRR, but distancing from reality institutions were highlighted together with the lack of training and continuing education that certainly weakens the possibilities of overcoming the alienation and fragmented knowledge, directly impacting the quality of services.